CENTRALISED DIAGNOSTICS OF ELECTRONIC AND ELECTRIC EQUIPMENT IN VEHICLES, ENGINE LIGHTING EQUIPMENT TESTING - Ježdík, Petr; Novák, Jiří (International Journal of Computing, 2014)
Today’s diagnostic systems used in vehicles are based on separate diagnostic subsystems for each electronic or electric device. The basic idea of the project is to develop a centralized diagnostic method to cover most of functional systems. The proposed method would expedite the overall testing time and bring other significant advantages such as savings on test equipment. This paper deals with engine lighting equipment testing technique. The fundamental idea is that both electronic and electric devices in a vehicle have a relationship to communication control busses. Each device can also be described as an electrical consumer with its typical power consumption characteristics. Hence, the proposed diagnostic method is based on investigating transient profile on power lines of a tested device whilst changing its state from off to on. The short time Fourier transform (STFT) processing is then applied to analyze the gained signal. The analysis results evaluate the condition of the engine lighting equipment.